2012
DOI: 10.1177/230949901202000304
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade Interlocking Nailing versus Dynamic Compression Plating for Humeral Shaft Fractures

Abstract: Both techniques were appropriate for treating humeral shaft fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
1
16
0
2
Order By: Relevance
“…13 Implant failure in plating may be explained by the stress rising at the end of the plate, 7 as well as the stress shielding of the bone by the plate at the fracture site which reduces the strength of the union and, it also provides less secure fixation especially in the osteopenic bone. 15 In the present study, a higher rate of reoperation was observed in plating group without a significant difference. This result was unlike the study conducted by Kumar et al, 1 where IMN had an increased rate of reoperations, also without a statistically significant difference.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…13 Implant failure in plating may be explained by the stress rising at the end of the plate, 7 as well as the stress shielding of the bone by the plate at the fracture site which reduces the strength of the union and, it also provides less secure fixation especially in the osteopenic bone. 15 In the present study, a higher rate of reoperation was observed in plating group without a significant difference. This result was unlike the study conducted by Kumar et al, 1 where IMN had an increased rate of reoperations, also without a statistically significant difference.…”
Section: Discussionsupporting
confidence: 41%
“…Kulkarni et al concluded that the overall complication rate was higher in the IMN group without a significant difference in their study. 15 But, overall significantly higher total complication rate in the plating group was observed in this study.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The most commonly used techniques are: osteosynthesis with plate and screws (LCP, locking compression plate) [5], the splint with intramedullary nail (IMN), and the external fixation (EF) [6]. These techniques have different biomechanical and physiological aspects, each with their advantages and disadvantages [7-12].…”
Section: Introductionmentioning
confidence: 99%